An Upper Miocene siliciclastic-carbonate ramp: depositional architecture, facies distribution, and diagenetic history (Capo Vaticano area, southern Italy) - Gramigna P.; Russo F.; BASSI, Davide (Facies, 2012)
During the Late Miocene, the marginal areas of the Mediterranean Basin were characterized by the development of mixed siliciclastic-carbonate ramps. This paper deals with a temperate siliciclastic-carbonate ramp (late Tortonian-early Messinian in age) which crops out in the Capo Vaticano area, Southern Apennines (Italy). Carbonate components are mainly represented by calcitic skeletal fragments of coralline red algae, bryozoans, bivalves, and larger foraminifera, whereas corals, brachiopods, echinoderms, and planktonic foraminifera are subordinate. In the studied ramp, the depositional geometries of the main unit, the 'Sabbie gialle ad Heterostegina', show a gradual steepening from low/middle (dip about 2-5°) to steep slope settings (up to 25°). The microfacies observations, the quantitative analyses of the main biogenic components as well as the rhodolith shapes and growth forms allowed the differentiation between the middle and the outer ramp depositional setting and the refining of the stratigraphic framework. The middle ramp is characterized by coralline red algal debris packstone facies often associated with larger foraminiferal floatstone/packstone facies, while the outer ramp is characterized by rhodolith floatstone/rudstone facies. These facies pass basinward into typical open-marine deposits (planktonic foraminiferal facies). The taxonomic composition of the coralline red algal assemblage points to a temperate paleoclimate and emphasizes the Miocene Mediterranean phytogeographic patterns. The absence of non-skeletal grains (ooids and green algae), the paucity of Porites patch reefs, the rare occurrence of primary marine cementation, all confirm that the studied ramp was poorly lithified within a warm-temperate setting. The flat depositional profile of the ramp can be related to the absence or paucity of primary marine carbonate cements. © 2011 Springer-Verlag.